Consumers’ Perception and Willingness to Pay for Cassava Leaves as a Leafy Vegetable in the Ejisu - Juaben Municipality, Ghana - Fred Nimoh; Stephen Prah; Karen Boansi (Agro Ekonomi, 2022)
Cassava leaves, as a leafy vegetable and highly nutritious food, is not a common traded leafy vegetable on the local markets of Ghana. The study assessed consumers’ perception and their willingness to pay (WTP) for cassava leaves as a leafy vegetable in the Ejisu-Juaben Municipality, a peri-urban district in the Ashanti region of Ghana. A multistage sampling technique was used to select 200 respondents for the study. Based on the empirical results, 67% of respondents were willing to pay for cassava leaves at various bids. Overall agreeing perception index (PI) was 64.6%, implying that respondents accept the cassava leaves to be sold at the local market as a leafy vegetable. On average, for every 500 grams bunch of cassava leaves, respondents were willing to pay GHS1.61 (USD0.32), below the value of its close substitute, spinach, at an initial bid of GHS2.00. An empirical tobit regression model revealed that consumers’ monthly income, level of education, and perception to sell cassava leaves as a leafy vegetable have significant influence on their WTP for cassava leaves as a leafy vegetable. The study recommends the need for farmers and other stakeholders to develop and promote the market for cassava leaves, as an alternative source of leafy vegetable for consumers and also as source of income to farmers. There is also the need for sensitization on the nutritional benefits and training on value addition to the produce to boost its patronage in the country and globally.